Whole-transcriptome analysis of differentially expressed genes between ray and disc florets and identification of flowering regulatory genes in Chrysanthemum morifolium - Liu, Hua; Jia, Yin; Chai, Yuhong; Wang, Sen; Chen, Haixia; Zhou, Xiumei; Huang, Conglin; Guo, Shuang; Chen, Dongliang (Frontiers in Plant Science, 2022)
Chrysanthemum morifolium has ornamental and economic values. However, there has been minimal research on the morphology of the chrysanthemum florets and related genes. In this study, we used the leaves as a control to screen for differentially expressed genes between ray and disc florets in chrysanthemum flowers. A total of 8,359 genes were differentially expressed between the ray and disc florets, of which 3,005 were upregulated and 5,354 were downregulated in the disc florets. Important regulatory genes that control flower development and flowering determination were identified. Among them, we identified a TM6 gene (CmTM6-mu) that belongs to the Class B floral homeotic MADS-box transcription factor family, which was specifically expressed in disc florets. We isolated this gene and found it was highly similar to other typical TM6 lineage genes, but a single-base deletion at the 3′ end of the open reading frame caused a frame shift that generated a protein in which the TM6-specific paleoAP3 motif was missing at the C terminus. The CmTM6-mu gene was ectopically expressed in Arabidopsis thaliana. Petal and stamen developmental processes were unaffected in transgenic A. thaliana lines; however, the flowering time was earlier than in the wild-type control. Thus, the C-terminal of paleoAP3 appears to be necessary for the functional performance in regulating the development of petals or stamens and CmTM6-mu may be involved in the regulation of flowering time in chrysanthemum. The results of this study will be useful for future research on flowering molecular mechanisms and for the breeding of novel flower types.